Absolute Stress Fields in the Source Region of the 1992 Landers Earthquake. Issue 10 (22nd October 2018) - Terakawa, Toshiko; Hauksson, Egill
Abstract: Earthquake focal mechanisms are often inverted to obtain the deviatoric stress field. Because shear stress is equal to the frictional strength of the fault at the time of an earthquake, six components of the absolute stress tensor at the hypocenter can be obtained from a focal mechanism by combining deviatoric stress fields with the Coulomb failure criterion. For a data set of focal mechanisms determined for southern California earthquakes, including the 1992 Landers earthquake sequence, we calculated the absolute stress tensors at their hypocenters using a standard intrinsic friction coefficient under three pore pressure conditions, parameterized by the reference pore pressure at the optimally oriented faults to the stress field. Three absolute stress fields were obtained for southern California immediately before the Landers main shock by applying each data set of the stress tensors to an inversion scheme based on Bayesian statistical inference and Akaike's Bayesian Information Criterion. The coseismic stress field was calculated to obtain the absolute stress fields immediately after the main shock. The variations of the coseismic stress rotation were related to the reference pore pressure. Comparing this relation with that obtained through stress inversion, we determined the absolute stress field and the most plausible reference pore pressure to be hydrostatic. On average, the maximum shear stresses immediately before the main shock were 44 ± 15 and 79 ± 24 MPa at depths of 5 and 10 km, respectively. Earthquakes on the off‐plate boundary faults in southern California occur on faults that are loaded by Anderson‐Byerlee stress conditions. Key Points: Absolute stress tensors were obtained from earthquake focal mechanisms by combining the stress pattern with the Coulomb failure criterion A method to model 3‐D absolute stress fields using focal mechanisms with a pore pressure parameter was developed The maximum shear stress in the source region of the Landers earthquake was estimated to be 44 ± 15 MPa at a depth of 5 km